2018
DOI: 10.1080/14767058.2018.1468881
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal hypoxic–ischemic encephalopathy: emerging therapeutic strategies based on pathophysiologic phases of the injury

Abstract: Neonatal hypoxic ischemic encephalopathy (HIE) is an important cause of neonatal death and disability. At present, there is no unified standard and specialized treatment method for neonatal HIE. In clinical practice, we have found that a gap remains between preclinical medical research and clinical application in the treatment of neonatal HIE. To promote an organic combination of preclinical research and clinical application, we propose the different phases as intervention targets, based on the pathophysiologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 34 publications
0
38
0
1
Order By: Relevance
“…Multicenter RCTs are investigation the neuroprotective effects of erythropoietin, allopurinol, xenon, melatonin, and topiramate when administrated alone or as adjuvants to TH [ 39 43 ]. Our survey found that 81% of the hospitals used one or more putative neuroprotective agents, including erythropoietin, ganglioside, rat nerve growth factor, citicoline, and cerebrolysin [ 44 – 48 ]. Clinical trials conducted in China and meta-analyses of these studies showed that ganglioside, the most commonly used agent in our survey, was safe and effective in reducing neurological sequelae of HIE [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Multicenter RCTs are investigation the neuroprotective effects of erythropoietin, allopurinol, xenon, melatonin, and topiramate when administrated alone or as adjuvants to TH [ 39 43 ]. Our survey found that 81% of the hospitals used one or more putative neuroprotective agents, including erythropoietin, ganglioside, rat nerve growth factor, citicoline, and cerebrolysin [ 44 – 48 ]. Clinical trials conducted in China and meta-analyses of these studies showed that ganglioside, the most commonly used agent in our survey, was safe and effective in reducing neurological sequelae of HIE [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Multicenter RCTs are investigation the neuroprotective effects of erythropoietin, allopurinol, xenon, melatonin, and topiramate when administrated alone or as adjuvants to TH [39][40][41][42][43]. Our survey found that 81% of the hospitals used one or more putative neuroprotective agents, including erythropoietin, ganglioside, rat nerve growth factor, citicoline, and cerebrolysin [44][45][46][47][48]. Clinical trials conducted in China and meta-analyses of these studies showed that ganglioside, the most commonly used agent in our survey, was safe and effective in reducing neurological sequelae of HIE [45].…”
Section: Discussionmentioning
confidence: 99%
“…Most of the studies lack data on long-term follow-up. Rat nerve growth factor, citicoline, and cerebrolysin were mainly evaluated by pre-clinical investigations and limited clinical studies [46][47][48]. Their neuroprotective effect remains to be demonstrated by multicenter RCTs.…”
Section: Discussionmentioning
confidence: 99%
“…Conceptually, brain injury caused by HI can be described in three phases [ 51 ]. The initial phase (primary energy failure) during which there is a decreased supply of oxygen and brain cells switch to anaerobic metabolism, which generates lactate and much less adenosine triphosphate (ATP) per molecule of glucose.…”
Section: Pathophysiology Of Preterm Brain Injurymentioning
confidence: 99%